Islam dan Psikoterapi Moden - Rajab, Khairunnas (Afkar: Jurnal Akidah dan Pemikiran Islam, 2006)
It is well known nowadays that modern psychotherapy produced by Western Psychology is an effective method in curing mental disorder. Nevertheless, delving into the true meaning and experience of Islamic spirituality, it can be suggested that Islam as the way of life also provides a unique approach in the treatment of mental disorder. This method can be developed by understanding and practicing the articles of faith ('Arkan al-lman), the articles of Islam ('Arkan al-lslam) and Islamic Sufism.